CIMIC in the ISAF mission: Conception, implementation and development of civil-military cooperation in the Bundeswehr abroad - Michael Paul (Stiftung Wissenschaft und Politik (SWP), 2009)
The concept of Civil-Military Co-operation (CIMIC) as seen in the Bundeswehr and NATO is to support the implementation of a military mission. As an integral part of the planning and conduct of military operations therefore, CIMIC has little to do with humanitarian or development aid. Popular images of soldiers drilling wells or erecting school tents, however, suggest that, when it comes to CIMIC activities, the Bundeswehr particularly distinguishes itself in the (re-)construction of infrastructure. However, it is neither realistic nor desirable for soldiers to act as 'aid workers.' In view of this discrepancy between operational reality and public perception, the nature and scope of CIMIC has elicited divisive discussion. Further conflict results from the fact that, as an self-protection measure, CIMIC is expedient and legitimate, however, the central task of armed forces in stabilization operations is to contribute to the creation of a safe and secure environment. In a deteriorating security situation such as in Afghanistan, the necessary degree of self-protection will inevitably have to be weighed against the establishment of security. In conclusion, it must be said that CIMIC has gained in operational significance. CIMIC has become an important contributory factor to the effectiveness of operations, especially in fluid security situations. Nonetheless without a sufficient military approach, CIMIC will not be enough. In order to increase the effectiveness of civil-military interaction, different suggestions are made concerning i.a. contingent rotations, sustainability, and operational restrictions
Keywords: 320